"Widziane", "czute" i "myślane". Kolory miasta w twórczości Władysława Stanisława Reymonta - Utkowska, Beata (Colloquia Litteraria, 2020)
This article attempt to analyze Reymont’s writings, paying particular attention to how he created urban space; most specifically, the author looks at the way in which Reymont used the palette of colours to depict the city in general. The author starts with a quote from Reymont’s letter to Antoni Wodziński: ‘Myself I consider everything I have written until “Chłopi” my literary introduction. These are the things that are seen, now it is time for what is felt, and later for the thought out’.The interpretation of the urban colour scheme in the novellas, “Ziemia Obiecana”, and “Wampir”, using three registers – a diachronic layout, referential optics, and in the context of the Young Poland mythology about the evils of the city – reveals that colour in Reymont’s prose on urban topics (with the exception of a few early texts) results from ‘the seen’ only to a limited degree, and that it is owed more to ‘the felt’ and ‘the thought out’. All this bears witness to the antirevolutionary views of Reymont and the Young Poland’s ‘urbanophobia’ and is a palpable sign of the historico-literary affectability of the period.